Inheritance of morpho-agronomic traits in ornamental peppers (Capsicum annuum L.) - Rêgo, Elizanilda Ramalho do; Fortunato, Flávia Laís Gomes; Carvalho, Michelle Gonçalves de; Santos, Cristine Agrine Pereira dos; Lima, José Ayron Moraes de; Rêgo, Mailson Monteiro do (Comunicata Scientiae, 2022)
Pepper have shown a growing and continuous acceptance by the consumer market, standing out in the trade of ornamental plants in pots. The objective of this study was to estimate the genetic parameters and gene effects involved in the inheritance of characters of size, flower and fruit in a segregating generation of ornamental pepper (Capsicum annuum L.). The experiment was carried out in a greenhouse, at the Plant Biotechnology Laboratory, at the Federal University of Paraíba. Two accessions of ornamental pepper (C. annuum L.) belonging to the vegetable germplasm bank of the Federal University of Paraíba were used as parents: UFPB 349 and UFPB 356. The experimental design was completely randomized, with five plants of each parent being evaluated, 20 plants of generation F1, 88 plants of generation F2 and 40 plants of RC1 and RC2. 19 quantitative characters referring to the plant, inflorescence and fruit were evaluated. The data obtained were subjected to generation analysis, and the effects of the models were subjected to the t test at a level of 5% and 1% significance. High values ​​of heritability in the broad and restricted sense were observed for plant height and pericarp thickness, suggesting the predominance of additive gene effects in character expression. The additive-dominant model (m, a, d) was adequate to explain the genetic parameters of most of the evaluated characteristics. However, for the canopy diameter, petal diameter, pedicel length and dry matter content, the additive-dominant model was inadequate, recommending the interpretation of the complete model. Keywords: Capsicum annuum, gene interaction, heritability